The contribution of the uncles and aunts in the life of their nephews/nieces in a public school of a neighborhood of the periphery of Salvador, Bahia State, Brazil (Research, Society and Development, 2020)
This research aims to fulfill gaps in the literature about the role of uncles / aunts in family contexts. Theoretical contributions came from studies on human ethology and family in society. The main objective was to investigate the role of the paternal and maternal aunts and uncles in the socialization of the nephews, seeking to identify the factors of care and protection in families belonging to the popular strata residing in the Suburban Railway of the city of Salvador, Bahia, after the nephews´ and nieces´ perspective. The specific objectives were: To investigate the place of uncles / aunts in the socialization of their nephews and nieces and their contribution as extended family members in their development; describe the activities related to the socialization processes exercised by the uncles / aunts. The study was a descriptive and exploratory quantitative research using a closed questionnaire and socio-demographic data. 206 students answered a closed questionnaire after a pre-study with 462 students to identify the presence of uncles/aunties and to collect general data about them. The main results revealed that the uncles' contribution was due to affective support, care activities and financial contribution. The aunts were the most mentioned by the nephews/nieces and uncles and aunts of matrilineal lineage received the highest percentages of mentions.  The conclusion was that the main role played by the uncles/aunts is affective and that the aunts are the most active in seeking the welfare of these children and adolescents. Further research, broadening the analysis and gathering information, is necessary.